2000
DOI: 10.1177/026765910001500109
|View full text |Cite
|
Sign up to set email alerts
|

Practical techniques Vacuum-assisted venous return in pediatric cardiopulmonary bypass

Abstract: Vacuum-assisted venous return (VAVR) has been reported to offer benefits for adults undergoing cardiopulmonary bypass (CPB), such as improved venous return, lowering priming volume (by eliminating the need to prime the venous line), and the use of smaller venous cannulae. All these benefits would be of particular value in pediatric perfusion because of the unique challenges of these smaller patients and the relatively large components of the CPB circuit. We have been using VAVR in children since the early summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, the experimental finding of an increased risk for systemic air embolism has to be kept in mind, and a careful evaluation of which technique is best to apply has to be performed in each individual case. In paediatric cardiac surgery, VAVD has been applied without complications by different groups [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…However, the experimental finding of an increased risk for systemic air embolism has to be kept in mind, and a careful evaluation of which technique is best to apply has to be performed in each individual case. In paediatric cardiac surgery, VAVD has been applied without complications by different groups [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…33 This technique has been shown to be safe with proven ability to reduce homologous blood transfusion in pediatric cardiac surgery. 3437…”
Section: Methodsmentioning
confidence: 99%
“…33 This technique has been shown to be safe with proven ability to reduce homologous blood transfusion in pediatric cardiac surgery. [34][35][36][37] Ultrafiltration. There are two forms of ultrafiltration.…”
Section: Operative Stagementioning
confidence: 99%
“…Small circuits with a remote pump head allow for a reduction in priming volume to 200 to 250 mL in neonates when 3/16 " tubing is used. Small circuits and assisted vacuum-assisted venous return (VAVR) 25 have made it possible to decrease the priming volume in both piglets 22 and in neonates 26 to 107 mL and to 190 mL, respectively. Personal experience and observations have shown that in a neonate with a 300 mL blood volume and a 45% Hct, Hct will decrease to 19% if the circuit priming volume is 400 mL with a clear prime; Hct will decrease to 27% if the circuit priming volume is only 200 mL.…”
Section: Nonpharmacological Methodsmentioning
confidence: 99%